Influence of carbon deficiency on phase formation and thermal stability of super-hard TaCy thin films. (May 2018) - Riedl, H.; Glechner, T.; Wojcik, T.; Koutná, N.; Kolozsvári, S.; Paneta, V.; Holec, D.; Primetzhofer, D.; Mayrhofer, P.H.
Abstract: Using nonreactive sputter deposition allows the preparation of single-phase fcc structured TaCy thin films over a wide compositional range with y between 0.63 and 1.04. Among this composition range, the C-deficient TaC0.78 exhibits the highest as deposited hardness of 43.4 ± 0.65 GPa combined with the highest thermal stability. Even after vacuum annealing to 2400 °C, no vacancy-ordered or faulted Ta-C based phases can be detected. The stabilization of carbon deficient fcc structured TaCy near y of about 0.75, revealed the decisive character of vacancy engineered thin films materials for ultra-high temperature applications. Graphical abstract: Unlabelled Image